Mo-Co-V-S microtube material and preparation method and application thereof
By preparing Mo-Co-V-S microtube materials, using the hollow structure and nanosheets, the existing transition metal sulfide electrochemical performance problem was solved, and a supercapacitor positive electrode material with high specific capacitance and energy density was achieved.
Patent Information
- Application Number
- CN202411861306.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-17
AI Technical Summary
The electrochemical performance of existing transition metal sulfides is low and it is difficult to meet the needs of high-performance supercapacitors.
Mo-Co-V-S microtube material is used as the positive electrode material of the supercapacitor, and hollow microtube structure and its densely distributed nanosheets are prepared by using rod-shaped MoO3 as a self-sacrificial template, combined with room temperature stirring and solvent heat.
The specific capacitance and energy density of the supercapacitor are improved, the electrochemical performance is enhanced, and the preparation method is simple to operate, low cost, and has no pollution to the environment.
Smart Images

Figure CN119673676A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of supercapacitor materials, and in particular to a Mo-Co-VS microtube material and a preparation method thereof, and application of the Mo-Co-VS microtube material in preparing a positive electrode material for a supercapacitor. Background Art
[0002] V2O5 has a unique layered structure and multiple oxidation states (V 2+ 、V 3+ 、V 4+ 、V 5+ ) and is different from other transition metal oxides; at the same time, due to its low development cost, abundant reserves, and high theoretical capacitance, V2O5 is considered to be the preferred material for electrode materials. However, V2O5's own shortcomings such as low conductivity and poor stability still make its practical application face a great challenge. The increasing global demand for energy has promoted the development of high-performance energy storage and conversion devices. Supercapacitors (SCs), also known as electrochemical capacitors, have received widespread attention in the fields of portable electronic products, hybrid vehicles, etc. due to their unique advantages such as low cost, high power, fast charge and discharge rate, and long life.
[0003] According to the charge storage mechanism, supercapacitors can be divided into electric double layer capacitors and pseudocapacitors. The former is a charge storage mechanism of electrostatic interaction, and the energy density is relatively low. In order to solve this problem, pseudocapacitors with fast redox reactions have become a research hotspot in the field of energy storage. Compared with electric double layer capacitors, pseudocapacitors have higher energy density.
[0004] Pseudocapacitive materials mainly include hydroxides, oxides, sulfides, selenides, nitrides, phosphides, etc. Among them, sulfides have more redox sites, higher specific capacitance and energy density, and are suitable as electrode materials for SCs. After sulfur replaces oxygen, its electronegativity decreases, the structure becomes more flexible, the electron transfer speed increases, and the electrochemical activity can be greatly improved. In addition, compared with monometallic sulfides, bimetallic sulfides exhibit lower energy barriers, thereby obtaining better electrochemical performance. This is because bimetallic sulfides improve the charge transfer between different ions and modify the electronic structure of the redox reaction. It can be seen that the introduction of appropriate elements can greatly improve the electrochemical properties of sulfides. From the above perspectives, the transition metal vanadium (V 2+ , V 3+ , V 4+ , V 5+ ) can enrich the redox reactions in the charge storage process. It is expected to improve the electrochemical performance of transition metal sulfides. Summary of the invention
[0005] Purpose of the invention: The purpose of the present invention is to provide a microtube material with excellent electrochemical properties, solving the problem of how to improve the electrochemical properties of transition metal sulfides. Another purpose of the present invention is to propose a method for preparing a microtube material, solving the problem of how to obtain the above-mentioned microtube material. The third purpose of the present invention is to propose the application of the microtube material in the preparation of a positive electrode material for a supercapacitor, solving the problem of how to prepare a positive electrode material.
[0006] Technical solution: The microtube material described in the present invention comprises hollow microtubes containing Mo, Co, V and S elements and nanosheets densely distributed on the surface of the hollow microtubes.
[0007] Preferably, the diameter of the hollow microtube is 500-600 nm, and the molar ratio of Mo, Co, V and S is 15.97:9.73:8.59:17.23.
[0008] The second aspect of the present invention discloses a method for preparing the above-mentioned microtube material, comprising the following steps:
[0009] (1) Dispersing rod-shaped MoO3 in an alcohol solvent, and then sequentially adding cobalt nitrate, an alcohol solution of 2-methylimidazole, and NaVO3, stirring the reaction, and then centrifuging to obtain a precipitate to obtain rod-shaped MoO3@ZIF-67@NaVO3;
[0010] (2) Dispersing rod-shaped MoO3@ZIF-67@NaVO3 in an organic solvent to obtain a suspension, adding thioacetamide to the suspension, performing a solvent thermal reaction, and centrifuging to obtain a precipitate to obtain a microtube material.
[0011] The preparation method of the present invention includes using MoO3 as a self-sacrificial template, combining room temperature stirring and solvent thermal methods, and successfully preparing a Mo-Co-VS microtube material, which has high specific capacitance and energy density as a supercapacitor positive electrode material.
[0012] Preferably, in step (1), the preparation method of rod-shaped MoO3 is: (NH4)6Mo7O 24 .4H2O is added to the nitric acid aqueous solution, heated for reaction, and then centrifuged to obtain the precipitate, which is then dried to obtain rod-shaped MoO3.
[0013] Preferably, in step (1), the alcohol solvent is an aqueous solution of at least one of methanol, ethanol and propanol, and the material-liquid ratio of the rod-shaped MoO3 to the alcohol solvent is 20-30 mg:10 mL.
[0014] Preferably, in step (1), the cobalt nitrate is Co(NO3)2·6H2O, the mass ratio of the rod-shaped MoO3, Co(NO3)2·6H2O, 2-methylimidazole and NaVO3 is 20-30:40-60:120-160:10-20, and the interval time for adding the rod-shaped MoO3, Co(NO3)2·6H2O, 2-methylimidazole and NaVO3 in sequence is at least 0.5-1h.
[0015] In some embodiments, the amount of MoO3 is in the range of 20-25 mg, the amount of Co(NO3)2·6H2O is in the range of 45-55 mg, the volume of the 2-methylimidazole alcohol solution is in the range of 5-10 mL, the mass concentration is in the range of 0.025-0.030 g / mL, the amount of NaVO3 is in the range of 15-20 mg, and the amount of thioacetamide is in the range of 45-55 mg. The alcohol solvent in the 2-methylimidazole alcohol solution can be selected from methanol, ethanol, propanol, etc.
[0016] Preferably, in step (1), the stirring reaction condition is stirring the reaction at room temperature for 0.5-12 hours, and the precipitate is washed alternately with deionized water and anhydrous ethanol and then dried to obtain rod-shaped MoO3@ZIF-67@NaVO3.
[0017] Preferably, in step (2), the organic solvent comprises at least one of dimethylformamide, tetrahydrofuran, dichloromethane and dimethyl sulfoxide; and the weight ratio of the rod-shaped MoO3@ZIF-67@NaVO3 to thioacetamide is 1:1-5.
[0018] Preferably, in step (2), the solvent thermal reaction is carried out at a constant temperature of 180-220° C. for 16-24 hours, and the precipitate is washed alternately with deionized water and anhydrous ethanol and then dried to obtain the microtube material.
[0019] The third aspect of the present invention discloses the use of the above-mentioned microtube material in preparing the positive electrode material of a supercapacitor.
[0020] The application includes using the Mo-Co-VS microtube material as an active working electrode material in a three-electrode system, using Pt wire as a counter electrode, Hg / HgO electrode as a reference electrode, and 3M potassium hydroxide KOH as an electrolyte. Then, using it as a positive electrode material of the second electrode, and using activated carbon as a negative electrode material.
[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0022] The present invention uses rod-shaped MoO3 as a self-sacrificial template to construct a hollow structure, which is conducive to the full contact between the electrolyte and the microscopic material. The Mo-Co-VS microtube material is successfully prepared by combining room temperature stirring and solvent thermal method, which can be used as an electrode material for supercapacitors. The introduction of Co, V, and S elements not only enriches the redox reaction of the microtube material, but also the synergistic effect of the Mo-Co-V ternary metal makes the electrode material have excellent electrochemical properties. The preparation method of the microtube material is simple and controllable, low in cost, and does not pollute the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is the microscopic characterization picture of rod-shaped MoO3;
[0024] Figure 2 This is the microscopic characterization diagram of Mo-S microtube material;
[0025] Figure 3 This is the three-electrode electrochemical performance diagram of Mo-S microtube material;
[0026] Figure 4 This is the microscopic characterization diagram of Mo-Co-S microtube material;
[0027] Figure 5 This is the three-electrode electrochemical performance diagram of Mo-Co-S microtube material;
[0028] Figure 6 This is the microscopic characterization diagram of Mo-VS microtube material;
[0029] Figure 7 This is the three-electrode electrochemical performance diagram of Mo-VS microtube material;
[0030] Figure 8 This is the microscopic characterization diagram of Co-VS microtube material;
[0031] Fig. 9 This is the three-electrode electrochemical performance diagram of Co-VS microtube material;
[0032] Fig.10 This is a microscopic characterization image of the Mo-Co-VS microtube material prepared in Example 1;
[0033] Fig.11 This is a three-electrode electrochemical performance diagram of the Mo-Co-VS microtube material prepared in Example 1;
[0034] Fig.12 The electrochemical performance diagram obtained when the Mo-Co-VS microtube material prepared in Example 1 is used as the positive electrode material and AC is used as the negative electrode material in a two-electrode system;
[0035] Fig.13This is a practical application diagram of the Mo-Co-VS microtube material prepared in Example 1 as the positive electrode material and AC as the negative electrode material (lighting up a small LED bulb). DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0037] Example 1: A method for preparing a Mo-Co-VS microtube material is as follows:
[0038] (1) According to the reported literature, rod-shaped MoO3 was synthesized as a template. The specific method is as follows:
[0039] Add 20 mL of deionized water and 2 mL of concentrated HNO3 to a 50 mL autoclave, and mix the solution evenly by ultrasonic treatment to obtain a nitric acid aqueous solution. 24 .4H2O was added to the nitric acid aqueous solution and stirred continuously for 30 minutes with a magnetic stirrer to form a colorless and transparent solution. It was then transferred to a stainless steel autoclave and placed in a constant temperature blast drying oven and heated to 200°C for 12 hours. After the reaction was completed, the temperature dropped to room temperature, and the white precipitate was collected in a 10mL centrifuge tube, and washed alternately with deionized water and anhydrous ethanol several times to remove other impurities, and finally transferred to a vacuum drying oven at 60°C for 12 hours. Rod-shaped MoO3 was thus obtained.
[0040] The synthesized MoO3 was simply characterized to confirm that its morphology and phase were basically the same as those reported in the literature. The low-magnification scanning electron microscopy and high-magnification transmission electron microscopy images of MoO3 are shown in Figure 2. Figure 1 As shown in Figures (a) and (b), it can be seen that the synthesized MoO3 is a rod-like structure with a diameter of 250nm. The X-ray powder diffraction pattern of MoO3 is shown in Figure 1 The middle (c) figure is consistent with MoO3 (JCPDS NO.05-0508).
[0041] (2) Preparation of Mo-Co-VS microtubule precursor: 25 mg of the above-mentioned rod-shaped MoO3 was dispersed in 10 mL of anhydrous methanol, and after 10 min of ultrasonic treatment, a uniformly dispersed white suspension was formed, which was then moved to a stirrer and stirred at room temperature to obtain a suspension. 50 mg of Co(NO3)2·6H2O was added to the suspension and stirred for 30 min until it dissolved and formed a light pink uniform mixed solution. Then 5 mL of anhydrous methanol solution containing 140 mg of 2-methylimidazole was slowly added to the mixture, stirred at room temperature for 30 min, and then 15 mg of NaVO3 was added. Stirring was continued for 12 h at room temperature. After the reaction was completed, the blue precipitate was collected in a 10 mL centrifuge tube, and washed alternately with deionized water and anhydrous ethanol for several times, and then dried in a vacuum drying oven at 60 ° C for 12 h to obtain rod-shaped MoO3@ZIF-67@NaVO3.
[0042] (3) Preparation of Mo-Co-VS microtubes: 20 mg of the above-synthesized rod-shaped MoO3@ZIF-67@NaVO3 was dispersed in 40 mL of dimethylformamide. After 15 min of ultrasonic treatment, a uniformly dispersed suspension was formed, which was then moved to a stirrer and stirred at room temperature. 50 mg of thioacetamide (TAA) was added to the mixed solution. After continuous stirring for 30 min, the mixed solution was transferred to a 50 mL autoclave and placed in a forced air drying oven and heated to 200 °C for 20 h. The reaction was then stopped, and after the temperature dropped to room temperature, the black precipitate product was collected in a 10 mL centrifuge tube, and washed alternately with deionized water and anhydrous ethanol for multiple times, and placed in a vacuum drying oven at 60 °C for 12 h to obtain the Mo-Co-VS microtube material.
[0043] Fig.10 Figures (a) and (b) are scanning electron microscope images and transmission electron microscope images of the product MoO3@ZIF-67@NaVO3 in step (2), respectively. It can be seen that the surface of the rod-shaped MoO3@ZIF-67@NaVO3 has uniform and sparse nanosheets, and the rod diameter is about 400nm. Fig.10 Figures (c) and (d) are scanning electron micrographs and transmission electron micrographs of the final product Mo-Co-VS microtubes, respectively. It can be seen that the final product Mo-Co-VS is a hollow microtube with a diameter of about 550nm and dense nanosheets on the surface. Fig.10Figure (e) in the middle is the X-ray powder diffraction pattern of the precursor MoO3@ZIF-67@NaVO3 and the product Mo-Co-VS microtubes. It can be seen that the diffraction peaks at 12.76°, 25.7°, 27.33°, 29.69° and 38.97° correspond to MoO3 (JCPDS No: 05-0508). The diffraction peaks at 17.8° and 26.84° correspond to NaVO3 (JCPDS No: 05-0508). The diffraction peak at 7.38° points to the characteristic peak of ZIF-67. According to the XRD results, the present invention successfully synthesized the precursor MoO3@ZIF-67@NaVO3. After TAA treatment, the product is transformed into an amorphous phase without diffraction peaks. Fig.10 Figure (f) in the middle is the EDS image of the product Mo-Co-VS microtube. It can be seen that the atomic ratio of Mo:Co:V:S is 15.97:9.73:8.59:17.23.
[0044] Example 2: A method for preparing a Mo-Co-VS microtube material is as follows:
[0045] (1) Preparation of Mo-Co-VS microtubule precursor: 20 mg of the rod-shaped MoO3 prepared in Example 1 was dispersed in 10 mL of anhydrous ethanol, and after 10 min of ultrasonic treatment, a uniformly dispersed white suspension was formed, which was then moved to a stirrer and stirred at room temperature to obtain a suspension. 40 mg of Co(NO3)2·6H2O was added to the suspension and stirred for 60 min until it dissolved and formed a light pink uniform mixed solution. Then 5 mL of anhydrous ethanol solution containing 120 mg of 2-methylimidazole was slowly added to the mixed solution, stirred at room temperature for 60 min, and then 10 mg of NaVO3 was added and stirred continuously at room temperature for 6 h. After the reaction was completed, the blue precipitate was collected in a 10 mL centrifuge tube, and washed alternately with deionized water and anhydrous ethanol for multiple times, and placed in a vacuum drying oven at 60 ° C for 12 h to obtain rod-shaped MoO3@ZIF-67@NaVO3.
[0046] (2) Preparation of Mo-Co-VS microtubes: 10 mg of the above-synthesized rod-shaped MoO3@ZIF-67@NaVO3 was dispersed in 40 mL of DMSO. After 15 min of ultrasonic treatment, a uniformly dispersed suspension was formed, which was then moved to a stirrer and stirred at room temperature. 50 mg of thioacetamide (TAA) was added to the mixed solution. After continuous stirring for 30 min, the mixed solution was transferred to a 50 mL autoclave and placed in a forced air drying oven and heated to 180 °C for 24 h. The reaction was then stopped, and after the temperature dropped to room temperature, the black precipitate product was collected in a 10 mL centrifuge tube, and washed alternately with deionized water and anhydrous ethanol for multiple times, and placed in a vacuum drying oven at 60 °C for 12 h to obtain the Mo-Co-VS microtube material.
[0047] Example 3: A method for preparing a Mo-Co-VS microtube material is as follows:
[0048] (1) Preparation of Mo-Co-VS microtubule precursor: 30 mg of the rod-shaped MoO3 prepared in Example 1 was dispersed in 10 mL of isopropanol and subjected to ultrasonic treatment for 10 min to form a uniformly dispersed white suspension, which was then moved to a stirrer and stirred at room temperature to obtain a suspension. 60 mg of Co(NO3)2·6H2O was added to the suspension and stirred for 30 min until it dissolved and formed a light pink uniform mixed solution. Then 5 mL of anhydrous methanol solution containing 160 mg of 2-methylimidazole was slowly added to the mixed solution. After stirring at room temperature for 30 min, 20 mg of NaVO3 was added and stirred continuously for 0.5 h at room temperature. After the reaction was completed, the blue precipitate was collected in a 10 mL centrifuge tube and washed alternately with deionized water and anhydrous ethanol for multiple times, and then placed in a vacuum drying oven at 60 ° C for 12 h to obtain rod-shaped MoO3@ZIF-67@NaVO3.
[0049] (2) Preparation of Mo-Co-VS microtubes: 50 mg of the above-synthesized rod-shaped MoO3@ZIF-67@NaVO3 was dispersed in 40 mL of dimethylformamide. After 15 min of ultrasonic treatment, a uniformly dispersed suspension was formed, which was then moved to a stirrer and stirred at room temperature. 50 mg of thioacetamide (TAA) was added to the mixed solution. After continuous stirring for 30 min, the mixed solution was transferred to a 50 mL autoclave and placed in a forced air drying oven and heated to 220 °C for 16 h. The reaction was then stopped, and after the temperature dropped to room temperature, the black precipitate product was collected in a 10 mL centrifuge tube, and washed alternately with deionized water and anhydrous ethanol for multiple times, and placed in a vacuum drying oven at 60 °C for 12 h to obtain the Mo-Co-VS microtube material.
[0050] Comparative Example 1: The preparation method of Mo-S microtube material is as follows:
[0051] Solvothermal sulfurization: The rod-shaped MoO3 (25 mg) prepared in Example 1 was dispersed in 40 mL of dimethylformamide. After 15 min of ultrasonic treatment, a uniformly dispersed suspension was formed, which was then moved to a stirrer and stirred at room temperature. Then 50 mg of TAA was added to the solution, and after continuous stirring for 30 min, the mixed solution was transferred to a 50 mL high-pressure reactor, placed in a forced air drying oven and heated to 200 ° C for 20 h. The reaction was then stopped, and after the temperature dropped to room temperature, the black precipitate product was collected in a 10 mL centrifuge tube, and washed alternately with deionized water and anhydrous ethanol for several times, and placed in a vacuum drying oven at 60 ° C for 12 h. Mo-S microtube material was obtained.
[0052] Figure 2 Figures (a) and (b) are scanning electron microscope images of Mo-S microtubes at different magnifications; it can be seen that after sulfurization, MoO3 is transformed into a hollow microtube structure (Mo-S), and its surface is transformed into a slightly thick nanosheet structure. Figure 2 Figure (c) is the X-ray powder diffraction pattern of Mo-S microtubes; it can be seen that there is a weak peak at about 9° in the figure. According to the reported literature description, the above peak is attributed to the (001) crystal plane of a new unresolved MoS2 phase. Figure 2 Figure (d) in the middle is the EDS image of Mo-S microtubes. It can be seen that the molar ratio is Mo:S=1:1.
[0053] Comparative Example 2: The preparation method of Mo-Co-S microtube material is as follows:
[0054] Preparation of Mo-Co-S precursor (MoO3@ZIF-67): The rod-shaped MoO3 (25 mg) prepared in Example 1 was dispersed in 10 mL of anhydrous methanol and subjected to ultrasonic treatment for 10 min to form a uniformly dispersed white suspension, which was then moved to a stirrer and stirred at room temperature. 50 mg of Co(NO3)2 was added to the suspension. . 6H2O, stirred until dissolved and formed a light pink uniform suspension. 5mL of methanol solution containing 140mg of 2-methylimidazole was slowly added to the mixture and stirred continuously for 12h at room temperature. After the reaction was completed, the blue precipitate was collected in a 10mL centrifuge tube, and washed alternately with deionized water and anhydrous ethanol for several times, and dried in a vacuum drying oven at 60℃ for 12h to obtain rod-shaped MoO3@ZIF-67.
[0055] Solvothermal sulfurization: The rod-shaped MoO3@ZIF-67 synthesized above was dispersed in 40 mL of dimethylformamide. After 15 minutes of ultrasonic treatment, a uniformly dispersed suspension was formed, which was then moved to a stirrer and stirred at room temperature. 50 mg of TAA was added to the mixed solution in sequence. After continuous stirring for 30 minutes, the mixed solution was transferred to a 50 mL high-pressure reactor and placed in a blast drying oven and heated to 200 ° C for 20 hours. The reaction was then stopped, and after the temperature dropped to room temperature, the black precipitate product was collected in a 10 mL centrifuge tube, and washed alternately with deionized water and anhydrous ethanol for several times, and placed in a vacuum drying oven at 60 ° C for 12 hours. Mo-Co-S microtube material was obtained.
[0056] Figure 4 Figures (a) and (b) are scanning electron micrographs of the precursor MoO3@ZIF-67 and Mo-Co-S microtubes, respectively. It can be seen that Figure 4 (a) The particles on the rods in the figure are ZIF-67 dodecahedrons, which are transformed into hollow microtubes with nanosheets on the surface after sulfurization (e.g. Figure 4(as shown in Figure (b)). Figure 4 Figure (c) is the X-ray powder diffraction pattern of MoO3@ZIF-67 and Mo-Co-S in this example; it can be seen that a very weak diffraction peak also appears at 9°, which can correspond to the (001) crystal plane of a new unresolved MoS2 phase. There is no diffraction peak for Co-S, indicating that Co-S is an amorphous structure. Figure 4 Figure (d) is the EDS image of the Mo-Co-S microtube material. It can be seen that the atomic molar ratio is Mo:Co:S=13.13:5.76:12.99.
[0057] Comparative Example 3: The preparation method of Mo-VS microtube material is as follows:
[0058] Preparation of Mo-VS precursor (MoO3@NaVO3): The rod-shaped MoO3 (25 mg) prepared in Example 1 was dispersed in 10 mL of anhydrous methanol, and subjected to ultrasonic treatment for 10 min to form a uniformly dispersed white suspension, which was then moved to a stirrer and stirred at room temperature. 15 mg of NaVO3 was added and stirred continuously for 12 h at room temperature. After the reaction was completed, the blue precipitate was collected in a 10 mL centrifuge tube, and washed alternately with deionized water and anhydrous ethanol for several times, and placed in a vacuum drying oven at 60 ° C for 12 h to obtain rod-shaped MoO3@NaVO3.
[0059] Solvothermal sulfurization: The rod-shaped MoO3@NaVO3 synthesized above was dispersed in 40 mL of dimethylformamide. After 15 minutes of ultrasonic treatment, a uniformly dispersed suspension was formed, which was then moved to a stirrer and stirred at room temperature. 50 mg of TAA was added to the mixed solution in sequence. After continuous stirring for 30 minutes, the mixed solution was transferred to a 50 mL high-pressure reactor and placed in a blast drying oven and heated to 200 ° C for 20 hours. The reaction was then stopped, and after the temperature dropped to room temperature, the black precipitate product was collected in a 10 mL centrifuge tube, and washed alternately with deionized water and anhydrous ethanol for several times, and placed in a vacuum drying oven at 60 ° C for 12 hours. Mo-VS microtube material was obtained.
[0060] Figure 6 Figures (a) and (b) are scanning electron microscope images of MoO3@NaVO3 and Mo-VS respectively; it can be seen that Figure 6 (a) The particles on the rods in the figure are ZIF-67 dodecahedrons, which are transformed into hollow microtubes with nanosheets on the surface after sulfurization (see Figure 6 (middle (b) figure). Figure 6 Figure (c) shows the X-ray powder diffraction patterns of the precursor MoO3@NaVO3 and Mo-VS microtubes; the intensity of the diffraction peak shows that MoO3@NaVO3 has good crystallinity, but after sulfurization it becomes amorphous Mo-VS. Figure 6Figure (d) is the EDS image of Mo-VS microtubes. It can be seen that the atomic molar ratio is Mo:V:S=15.75:9.27:14.14.
[0061] Comparative Example 4: The preparation method of Co-VS microtube material is as follows:
[0062] Preparation of Co-VS precursor (ZIF-67@NaVO3): 50 mg of Co(NO3)2 . 6H2O, dispersed in 10mL of anhydrous methanol, after 10min of ultrasonic treatment, stirred until dissolved and formed a light pink uniform suspension. 5mL of methanol solution containing 140mg of 2-methylimidazole was slowly added to the mixture, stirred at room temperature for 30min, and then 15mg of NaVO3 was added. Stirring was continued for 12h at room temperature. After the reaction was completed, the blue precipitate was collected in a 10mL centrifuge tube, and washed alternately with deionized water and anhydrous ethanol for several times, and placed in a vacuum drying oven at 60℃ for 12h to obtain dodecahedral ZIF-67@NaVO3.
[0063] Solvothermal sulfurization: The synthesized dodecahedral ZIF-67@NaVO3 was dispersed in 40 mL of dimethylformamide, and after 15 min of ultrasonic treatment, a uniformly dispersed suspension was formed, which was then moved to a stirrer and stirred at room temperature. 50 mg of TAA was added to the mixed solution in sequence, and after continuous stirring for 30 min, the mixed solution was transferred to a 50 mL high-pressure reactor, placed in a blast drying oven and heated to 200 ° C for 20 h. The reaction was then stopped, and after the temperature dropped to room temperature, the black precipitate product was collected in a 10 mL centrifuge tube, and washed alternately with deionized water and anhydrous ethanol for several times, and placed in a vacuum drying oven at 60 ° C for 12 h. The Co-VS microtube material was obtained.
[0064] Figure 8 Figures (a) and (b) are scanning electron micrographs of the precursor ZIF-67@NaVO3 and Co-VS microtubes, respectively. It can be seen that after sulfurization, the solid dodecahedron structure is transformed into a hollow porous dodecahedron with small particles on the surface (see Figure 8 (middle (b) figure). Figure 8 Figure (c) shows the X-ray powder diffraction pattern of ZIF-67@NaVO3 and Co-VS microtubes; it can be seen that ZIF-67@NaVO3 has good crystallinity and becomes amorphous Co-VS after sulfurization. Figure 8 Figure (d) in the middle is the EDS image of Co-VS microtubes. It can be seen that the atomic molar ratio obtained by EDS analysis is Co:V:S=11.54:9.32:10.1.
[0065] In the above technical scheme, in order to prove that Mo-Co-VS microtubes have excellent specific capacitance performance when used as positive electrode materials in supercapacitors, the following performance tests are performed:
[0066] The final products prepared in Example 1 and Comparative Examples 1-4 were used as electrode positive electrode materials in a three-electrode performance test. The three electrodes included a microtube material as the positive electrode in the three electrodes, a Pt wire as the counter electrode, a Hg / HgO electrode as the reference electrode, and 3M potassium hydroxide KOH as the electrolyte. Subsequently, the Mo-Co-VS microtube material was used as the positive electrode material of the second electrode, and activated carbon was used as the negative electrode material, and was applied to the two-electrode performance test.
[0067] The electrochemical performance of supercapacitors is mainly characterized by testing methods such as cyclic voltammetry (CV), constant current charge and discharge (GCD) and impedance spectroscopy (EIS). Its key performance indicators include specific capacity, energy density, power density and cycle stability. The most important parameter is the specific capacity, which represents the energy storage capacity of supercapacitors.
[0068] The test results are as follows Figure 3 , 5 , 7, 9, 11, 12, 13, Figure 3 Figures (a) and (b) are the cyclic voltammetry curve and constant current charge-discharge diagram of Mo-S microtubes, respectively; Figure 3 Figures (c) and (d) are the rate performance diagram and impedance diagram of Mo-S microtubes, respectively. Figure 3 As shown in Figures (a) and (b), when Mo-S microtubes are used as electrode materials in three electrodes, the current density is 1Ag -1 The specific capacitance of the material reaches 60.5 F g -1 ;Depend on Figure 3 As can be seen in Figure (c), the rate performance of Mo-S microtubes as electrode materials is poor when applied to three electrodes; Figure 3 Figure (d) shows the impedance spectrum of Mo-S microtubes when used as electrode materials in three electrodes. From the curve, it can be observed that the radius of the semicircle appearing in the high-frequency region is larger, indicating that the resistance of the Mo-S electrode material is larger and the internal resistance of the electrode is larger, but the slope of the straight line in the low-frequency region is smaller, indicating that the diffusion resistance of the electrolyte is larger; therefore, the electrochemical performance of Mo-S microtubes as electrode materials is poor, and they are not ideal supercapacitor electrode materials.
[0069] Figure 5 Figures (a) and (b) in the middle are the cyclic voltammetry curve and constant current charge-discharge diagram of the Mo-Co-S microtube material, respectively; Figure 5 Figures (c) and (d) are the rate performance diagram and impedance diagram of Mo-Co-S microtube material, respectively. Figure 5As shown in Figures (a) and (b), when Mo-Co-S microtubes are used as electrode materials in three electrodes, the current density is 1A g -1 The specific capacitance of the material reaches 575F g -1 ;Depend on Figure 5 The middle (c) figure shows that the rate performance of Mo-Co-S microtubes as electrode materials is good (74.4%) when applied to three electrodes; Figure 5 Figure (d) in the middle is the impedance spectrum of Mo-Co-S microtubes when used as electrode materials in three electrodes. From the curve, it can be observed that the radius of the semicircle appearing in the high-frequency region is smaller than that of Mo-S, and the electrode internal resistance is average, but the slope of the straight line in the low-frequency region is average, indicating that the diffusion resistance of the electrolyte is average; therefore, the electrochemical performance of Mo-Co-S microtubes as electrode materials is average, and it is not an ideal supercapacitor electrode material.
[0070] Figure 7 Figures (a) and (b) are the cyclic voltammetry curve and constant current charge-discharge diagram of Mo-VS microtube material, respectively; Figure 7 Figures (c) and (d) are the rate performance diagram and impedance diagram of Mo-VS microtube material respectively; Figure 7 As shown in Figures (a) and (b), when Mo-VS microtubes are used as electrode materials in three electrodes, the current density is 1A g -1 Under this condition, the specific capacitance of the material reaches 755F g -1 ;Depend on Figure 7 From the figure (c), it can be concluded that the rate performance of Mo-Co-S microtubes as electrode materials is poor (24.2%) when applied to three electrodes; Figure 7 Figure (d) shows the impedance spectrum of Mo-Co-S microtubes when used as electrode materials in three electrodes. From the curve, it can be observed that the radius of the semicircle appearing in the high-frequency region is smaller than that of Mo-S microtubes and Mo-Co-S microtubes, and the electrode internal resistance is average, but the slope of the straight line in the low-frequency region is average, indicating that the diffusion resistance of the electrolyte is average; therefore, the electrochemical performance of Mo-VS microtubes as electrode materials is average. Although it is slightly higher than the specific capacitance of Mo-Co-S materials, it is still not an ideal supercapacitor electrode material.
[0071] Fig. 9 Figures (a) and (b) are the cyclic voltammetry curve and constant current charge-discharge diagram of Co-VS microtubes, respectively; Fig. 9 Figures (c) and (d) are the rate performance diagram and impedance diagram of Co-VS microtubes, respectively. Fig. 9 As shown in Figures (a) and (b), when Co-VS microtubes are used as electrode materials in three electrodes, the current density is 1A g -1 Under this condition, the specific capacitance of the material reaches 370Fg -1 ;Depend on Fig. 9 The middle (c) figure shows that the rate performance of Co-VS microtubes as electrode materials is poor (53.0%) when applied to three electrodes; Fig. 9 Figure (d) shows the impedance spectrum of Co-VS microtubes when used as electrode materials in three electrodes. From the curve, it can be observed that the radius of the semicircle appearing in the high-frequency region is smaller than that of Mo-S microtubes, but larger than Mo-Co-S microtubes and Mo-VS microtubes; the electrode internal resistance is average, and the slope of the straight line in the low-frequency region is large, indicating that the diffusion resistance of the electrolyte is large; the electrochemical performance of this electrode material is poor, although it is slightly higher than the specific capacitance of Mo-S microtube materials, but Co-VS microtube materials are not ideal supercapacitor electrode materials.
[0072] Fig.11 Figures (a) and (b) are the cyclic voltammetry curve and constant current charge-discharge diagram of Mo-Co-VS microtubes, respectively; Fig.11 Figures (c) and (d) are the rate performance diagram and impedance diagram of Mo-Co-VS microtubes, respectively. Fig.11 As shown in Figures (a) and (b), when Mo-Co-VS microtubes are used as electrode materials in three electrodes, the current density is 1A g -1 Under this condition, the specific capacitance of the material reaches 1655F g -1 ;Depend on Fig.11 The middle (c) figure shows that the rate performance of Mo-Co-VS microtubes as electrode materials is good (50.5%) when applied to three electrodes; Fig.11 Figure (d) shows the impedance spectrum of Mo-Co-VS microtubes as electrode materials for three electrodes. From the curve, it can be observed that the semicircle radius and the intercept with the x real axis in the high-frequency region are small, indicating that the charge transfer resistance and electrode internal resistance of the Mo-Co-VS microtube electrode material are small; the slope of the straight line in the low-frequency region is large, indicating that the kinetic process of this electrode material is fast. Its electrochemical performance is better than that of Mo-S microtubes, Mo-Co-S microtubes, Mo-VS microtubes and Co-VS microtubes, and it is the most ideal supercapacitor electrode material.
[0073] Fig.12 The electrochemical performance test diagram is that the electrodes are made of Mo-Co-VS microtubes as positive electrode materials and AC as negative electrode materials, and the two electrodes are assembled into two electrodes. The two electrodes are tested at 1, 2, 3, 5, 7, and 10 A g -1 The specific capacitances at current densities of 170, 159, 149.9, 135.3, 119.4 and 100 F g -1 . Fig.12 Figures (a) and (b) are the cyclic voltammetry curves and constant current charge-discharge diagrams of the two electrodes, respectively; Fig.12Figures (c) and (d) are the rate performance and power energy density diagrams of the two electrodes, respectively. It can be seen that the two electrodes can withstand currents up to 10A g -1 When the power density is 0.8kW kg -1 The energy density of the device is 60.5W hkg -1 Even when the power density rises to 8.0kW kg -1 , still able to provide 35.6W h kg -1 High energy density.
[0074] Fig.13 The figure is a practical application diagram (lighting up LED) of Mo-Co-VS microtubes as positive electrode materials and AC as negative electrode materials, which proves that the present invention has practical application prospects.
Claims
1. A microtube material, characterized in that: It includes hollow microtubes containing Mo, Co, V and S elements and nanosheets densely distributed on the surface of the hollow microtubes.
2. The microtube material according to claim 1, characterized in that: The diameter of the hollow microtube is 500-600 nm, and the molar ratio of Mo, Co, V and S is 15.97:9.73:8.59:17.
23.
3. The method for preparing the microtube material according to claim 1 or 2, characterized in that: The steps include: (1) Dispersing rod-shaped MoO3 in an alcohol solvent, and then sequentially adding cobalt nitrate, an alcohol solution of 2-methylimidazole, and NaVO3, stirring the reaction, and then centrifuging to obtain a precipitate to obtain rod-shaped MoO3@ZIF-67@NaVO3; (2) Dispersing rod-shaped MoO3@ZIF-67@NaVO3 in an organic solvent to obtain a suspension, adding thioacetamide to the suspension, performing a solvent thermal reaction, and centrifuging to obtain a precipitate to obtain a microtube material.
4. The method for preparing the microtube material according to claim 3, characterized in that: In step (1), the preparation method of rod-shaped MoO3 is: (NH4)6Mo7O 24 .4H2O is added to the nitric acid aqueous solution, heated for reaction, and then centrifuged to obtain the precipitate, which is then dried to obtain rod-shaped MoO3.
5. The method for preparing the microtube material according to claim 3, characterized in that: In step (1), the alcohol solvent is at least one of methanol, ethanol and propanol, and the material-liquid ratio of the rod-shaped MoO3 to the alcohol solvent is 20-30 mg:10 mL.
6. The method for preparing the microtube material according to claim 3, characterized in that: In step (1), the cobalt nitrate is Co(NO3)2·6H2O, the mass ratio of the rod-shaped MoO3, Co(NO3)2·6H2O, 2-methylimidazole and NaVO3 is 20-30:40-60:120-160:10-20, and the interval time for adding the rod-shaped MoO3, Co(NO3)2·6H2O, 2-methylimidazole and NaVO3 in sequence is at least 0.5-1h.
7. The method for preparing the microtube material according to claim 3, characterized in that: In step (1), the stirring reaction condition is stirring the reaction at room temperature for 0.5-12 hours, and the precipitate is washed alternately with deionized water and anhydrous ethanol and then dried to obtain rod-shaped MoO3@ZIF-67@NaVO3.
8. The method for preparing the microtube material according to claim 3, characterized in that: In step (2), the organic solvent includes at least one of dimethylformamide, tetrahydrofuran, dichloromethane, and dimethyl sulfoxide; and the weight ratio of the rod-shaped MoO3@ZIF-67@NaVO3 to thioacetamide is 1:1-5.
9. The method for preparing the microtube material according to claim 3, characterized in that: In step (2), the solvent thermal reaction is carried out at a constant temperature of 180-220° C. for 16-24 hours, and the precipitate is washed alternately with deionized water and anhydrous ethanol and then dried to obtain a microtube material.
10. Use of the microtube material according to claim 1 or 2 in preparing a positive electrode material for a supercapacitor.
Citation Information
Patent Citations
Aerogel material composed of fibers and adhesive, and preparation method and application thereof
CN107868270A
Hybrid heat radiating sheet based on carbon nanotube and fabrication method thereof
KR1020160095519A
Multi-layer based new conceptual battery type supercapacitor with high power density and high energy density and method for preparing the same
US20160086740A1